IN VITRO PRODUCTION OF SOME TERPENOIDS COMPOUNDS FROM Nigella sativa WITH DIFFERENT EXPLANTS TYPE AND PEG CONCENTRATIONS - Neamah, S. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This experiment was conducted to study the effect of explant and poly ethylene glycol (PEG) on the production  of monoterpeniods compounds in the callus of Nigella sativa. The explant type had a significant effect on callus induction from the hypocotyl giving a significant increase on fresh and dry weight of 282.8 and 25.25 mg. respectively. as well, as the production of the borneol compound at 26.70 µg.100mg-1 dry weight.The callus inducted from the cotyledon has a significant increase of the thujone, α-pinene, camphene and carvacrol compounds at 24.01, 20.58, 13.58 and 23.80 µg.100mg-1 dry weight, respectively. The increasing concentrations of PEG resulted in a significant reduction in fresh and dry weight. Also, the addition of PEG stimulated the production of terpeniods with the PEG concentration of 100g.L-1 producing the highest amount of  borneol and carvacrol at 36.60 and 37.80 µg.100mg-1 dry weight. Meanwhile, 150 g.L-1 PEG treatment produced the highest  amount of thujone, α-pinene, camphene and mycene at 23.29, 21.13, 14.45 and 12.45 µg.100mg-1 dry weight, respectively. The interaction between the two factors was significant, with the callus inducted from cotyledon treated with 100 g.L-1 of PEG, showed the highest production of thujone,  α-pinene and carvacrol at 27.57, 29.33 and 47.20 µg.100mg-1 dry weight. Limonene reached 14.96 µg.100mg-1 dry weight, at 150g.L-1 of PEG treatment in callus inducted from the hypocotyl.